Geometrical Effects of Conic Sections on The Motion of Bodies - B. Hamid, Abdel Rahim (Gezira Journal of Engineering and Applied Sciences, 2018)
The subject of dynamics is generally divided into two branches; kinematics which is concerned with the geometry of motion apart from all considerations of force, mass or energy. And kinetics which is concerned with the effects of forces on the motion of bodies. In this paper, we explained the basic geometrical concepts of the conic sections (ellipse, parabola, and hyperbola) and their effects on the suitable kind of motion and the orbits of bodies.